ANALISIS MAKNA SIMBOLIK DAN NILAI SPIRITUAL DALAM TRADISI NYONGEK BUDAK (MEMANDIKAN BUDAK) DI DESA RAMBUTAN MASAM PROVINSI JAMBI - Salsabela, Wesi; Siti Aminah; Cici Elisabeth Sitanggang; Zahratul Jannah; Aulia Fitriana Adrian; Ulin Khusnul Hotimah; Nabila Anastasya; Ifdah Aulia; Geby Chirlda Putri Abdi; Kartika Meilani; Aulia Argierta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Nyongek Budak tradition in Rambutan Masam Village, Jambi Province, is a Malay customary ritual that is still preserved. This study aims to describe the implementation of the tradition, analyze the symbolic meaning of the ritual equipment, and identify the spiritual values contained therein. The research uses a descriptive qualitative approach through interviews with two traditional leaders and documentation of the ritual procession on February 6, 2026. The results of the study show that each item has a symbolic meaning that represents growth, tranquility, purification, strength of character, protection, and the beauty of life. This tradition contains spiritual values in the form of protection, hope for the future, steadfastness in life, and early spiritual education, while also strengthening cultural identity and preserving local wisdom.